Georgia Architectural and Historic Properties Survey of Rural [005] Southeast Brooks Co., Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [005] Southeast Brooks Co., Ga. December 1980. One story house of rectangular plan. Gabled, tin roof. Square posts at shed porch. Exposed rafters. Shiplap siding. Double hung sash windows with 4/4 lights. Exterior chimney. Concrete piers. Dirt yard. Several small sheds. Date of Construction: unknown. Typical rural farmhouse common to Brooks Co. area.
One story house of rectangular plan. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 837 KB (857,308 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)